Olivier Messiaen's opera, Saint François d'Assise - Benitez, Vincent Perez, 1955- (Indiana University Press, 2019)
In this comprehensive study of Olivier Messiaen's magnum opus, Saint François d'Assise, Vincent Perez Benitez examines the opera from both theological and musical-analytical perspectives to ask how Messiaen expresses his Catholic theology through his work.